Efecto de la posicion de la estaca, niveles de control de malezas y arreglo espacial sobre competencia entre malezas y yuca y el rendimiento de la yuca, variedad M Col 22 - Anzules T, V (International Center for Tropical Agriculture, 1981)
Research was conducted at the Centro Internacional de Agricultura Tropical (CIAT) in 1980 in order to solve the problem of low cassava yields in Loja, Ecuador, Objectives were: (1) to determine the effect of vertical and horizontal plantings of cuttings on the emergence and competitive vigor of cassava; (2) to determine the effect of 3 levels of weed control on the cost of each practice and on cassava yields; and (3) assess the effect of spatial arrangements on the competitive ability of cassava regarding weeds, keeping a constant population. A total of 3072 cuttings, of var. M Col 22 were used in a split-plot design with 12 treatments and 4 replications. Treatments were: 1 x 1 m and 0.7 x 0.7 m spacings for populations of 20,000 and 20,408 plants/ha, resp.; vertical and horizontal planting positions; and weed control: (a) weeding at 3O days; (b) 3 weedings at 3O,60, and 9O days; and (c) preemergent control + one weeding. The percentage of germination, coverage/crop and coverage/weed, yield and its components, DM and starch contents were determined. The highest av. yield (40.2 t/ha) was obtained with vertical planting in the 0.7 x0.7 m system with just one weeding. No differences were observed among yields regarding the different levels of weed control. It was concluded that a good cultural control of weeds and good yields can be obtained with var. with little or intermediate vigor if they are planted in quadratic arrangements and in high populations. (CIAT)